Seismic vulnerability assessment of Portuguese adobe buildings - Momin, Samar (2021)
Adobe construction represents 5.3% of the total Portuguese building stock according to the latest National Housing Census. The distribution of these adobe buildings is scattered across the country, with higher density in the central region and in Algarve in the south, where the seismic hazard is highest. A large proportion of these buildings are still in use for residential and commercial purposes and are of historical significance, contributing to the cultural heritage of the country. Adobe buildings are known to exhibit low seismic resistance due to their brittle behavior, thus making them vulnerable to ground shaking and more prone to structural damage that can potentially cause human fatalities. Three buildings with one-story, two-stories, and two-stories plus an attic were numerically modeled using solid and contact elements. Calibration and validation of material properties were carried out following experimental results. A set of 30 ground motion records with bi-directional components were selected, and non-linear time-history analyses were performed until complete collapse occurred. Two novel engineering demand parameters (EDPs) were used, and damage thresholds were proposed. Finally, fragility and fatality vulnerability functions were derived. These functions can be used directly in seismic risk assessment studies.